Alfred R. Wallace: from natural selection to social commitment (Culturas Científicas, 2018)
The figure of Alfred Russel Wallace has remained in relative obscurity in the history of science. His evolutionary vision focused mainly on the proposal of natural selection, a theory which he himself called Darwinism in 1889, in the book of the same name. This view was based on the first approaches of Wallace to naturalism, especially from readings such Malthus’ An Essay on the Principle of Population (1798), Lyell’s Principles of Geology (1830-1833) and Chambers’ Vestiges of the Natural History of the Creation (1844). His travels to the Amazon (1848-1852) and to the Malay Archipelago (1854-1862) were extremely useful in his search for evidences to explain the transmutation of species, and especially that of humans. A voracious reader and avid writer, Wallace had many interests, both in science and in society, which followed parallel ways his entire life. That unified view of evolution collided with the proposed new science that emerged from the mid-nineteenth century England, where science was conceived independently of other cultural aspects such as religion. This paper presents briefly the development of the evolutionary view of Wallace and his achievements in three key moments: the independent discovery of natural selection, which leads necessarily to raise the similarities and differences of Wallace’s proposal with respect to that of Charles Darwin. After that, the application of his particular evolutionary vision of Man, which was his main focus as an evolutionist, and whose boundaries are assumed were influenced by his involvement with spiritualism. The last section is a summary of how Wallace applied the idea of evolution in science and society, which leads us to conceive Wallace evolutionary proposal as a worldview.
Keywords: evolution; Alfred Russel Wallace; naturalism; society; science; darwinism